A comparative study between hysteroscopic findings and histopathology in cases of post-menopausal bleeding patients - Pati, Ipsita Priyadarshini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postmenopausal bleeding (PMB) is most common cause of gynecological visits. All with unexpected uterine bleeding should be evaluated for endometrial carcinoma. Although most cases in developing countries is due to atrophy. Aim of the study was to evaluate endometrial causes of postmenopausal bleeding with its correlation with hysteroscopy findings and endometrial tissue histopathology. Methods: A total 74 consecutive cases of PMB over a period of 1½ year fulfilling the inclusion and exclusion criteria and giving informed consent were selected. Each patient was subjected to transvaginal sonography (TVS) for assessment of uterus, adnexa and endometrial thickness. Then they were scheduled for hysteroscopy and dilation and curettage. Endometrial sample was sent for histopathological examination (HPE). Results: In our study, 48.65% of patients with postmenopausal bleeding where in age group menopause is 51-55 years. The TVS, hysteroscopy and histopathological findings were correlated in this study. On HPE 43.24% showed atrophic endometrium out of which maximum 93.93% were identified in hysteroscopy. Conclusions: In women with PMB, hysteroscopy is the basic tool that allows precise diagnosis of various endouterine pathologies. The average sensitivity of hysteroscopy was 98% in our study and the specificity was 96.4%. Hence, we can conclude that it is highly accurate for evaluating endometrial pathologies.